Environmentally and socially responsible behaviour of Generation Z in the context of the economy of the common good - Balińska, Agata; Jaska, Ewa; Werenowska, Agnieszka (Publishing House of Wroclaw University of Economics and Business, 2024)
The aim of the presented study was to analyse environmentally and socially responsible behaviour of Generation Z in the context of the economy of the common good. The main reasons for the choice of such issues were related to unfavourable climate change and the increasing participation of Gen Z in social, economic and political life. The specific character of this generation makes the common good and its conscious management correspond to a greater extent than ever before with the model proposed by Ostrom and Felber. The phenomenon of the common good is not sufficiently recognised. The study used the analysis of domestic and foreign literature as well as the results of the authors’ own empirical research. A questionnaire was carried out on a sample of 838 respondents from Generation Z (Zoomers) in 2023. The collected material was subjected to quantitative and qualitative analysis. An innovative methodological solution was the use of an original index of environmentally and socially responsible behaviour. According to the study, the value of this index changes depending on the socio-demographic variables of the respondents. The research fills a knowledge gap (analysis of environmentally and socially responsible behaviour) and a methodological gap (its own indicator).
Argumenta Oeconomica, 2024, Nr 2 (53), s. 90-106
Keywords: index of environmentally and socially responsible behaviour; generation Z; economy of the common good